The Influence of Psychological Triggers, Content Engagement, and Self-Regulation on the Relationship Between Social Media Ads and Impulsive Buying - Hannah Nichole V. Gonzales; Ralph Clarence M. Laraga; Niña Fatima Rainy B. Lopez; Mart Francesfil R. Paug; Sol Andrew L. Pegarido; Kyrah Alodia A. Yanson; Lalaine O. Narsico; Peter G. Narsico (International Journal of Multidisciplinary: Applied Business and Education Research, 2026)
Social media advertising has been extensively investigated as an influential factor to consumer behavior, but little research investigates how psychological triggers, content-driven factors, and self-regulation jointly influence impulsive buying. This gap is filled by an exploration of their joint influence. Experimental Design This study was quantitative, descriptive-correlational in nature, and comprised 392 university students in Cebu City, Philippines. An online survey that measured social media ad exposure, psychological triggers, content-driven influence, self-regulation, and impulsive buying was conducted. The reliability test resulted in Cronbach’s alpha of 0.8542. We employed regression analysis to evaluate relationships among variables. Respondents generally agreed with the statements that they were exposed to social media ads (M = 3.59) and practiced self-regulation (M = 3.86), while impulsive buying tendencies were neutral (M = 2.85). Moderately influential factors were psychological triggers (M = 3.22) and content-driven factors (M = 3.36). The multiple regression showed that the influence of psychological triggers and content-driven factors were the most positive with regard to impulsive buying, while self-regulation was negatively correlated. Exposure to social media ads was found to be less strongly, but significantly, positively associated. The full model accounted for 57% of the variance in impulsive buying. Implication is that impulsive purchasing is determined more by persuasive cues and psychological factors than exposure only, and self-regulation is a protective factor. Marketers should drive engagement for content and ethical action, educators and policy makers should promote financial literacy and self-discipline in their purchases to avoid acts of impulse.